Rerouting Framework for Sustainable Management in Elephant Conservation - Mohamad Abdullah, Nazirah; Rambat, Shuib; Othman, Amir Hamzah; Tugi, Astina; Nor Hassan, Nurul Hazirah; Saaban, Salman (Journal of Sustainable Natural Resources, 2023)
: Human-Elephant Conflict (HEC) has been identified as one of the major threats to wild elephants through its range in thirteen countries including Malaysia. With development encroaching into the elephant’s natural territories, the number of HEC cases has increased. The aim of this study is focusing on developing a framework of elephant rerouting and causeway using geomatics technology and 3D Geo-visualisation as strategy to conserve elephant in sustainable way for Taman Negara Rompin. The framework was used to propose alternative pathway based on rational model. Four main elements strongly highlighted in the rerouting framework are elephant diet’s sources, tracking trail, fencing and deterrents and the corridors monitoring. With the integration of Geographical Information system, the knowledge to protect elephants from HEC can be enhanced.